Investigating characteristics of head impacts in paediatric snowsport participants: using telemetry, GPS positioning and acceleration logging - Dickson, T. J.; Trathen, S.; Waddington, G. (Procedia Engineering, 2011)
This paper presents insights into the application and combination of two forms of data collection in the context of snowsport participation. The GPS Spi Elite and the HIT System were initially designed for use in field-based team sports. Using a case study approach this paper highlights the value of the two data sources for interpreting recorded head impacts and thus providing a more robust understanding of the characteristics of any impacts that may occur.